Parametric Study on Seismic Response of RCS Structures - Adel Fahim Rezkalla, Shady; Mohammed Parvez, Anwar; Jaganathan, Jayaprakash; Elleithy, Wael; Leong Lau, Teck; Lim Yap, Kian (International Journal of Engineering and Technology, 2018)
Reinforced concrete steel (RCS) moment resisting frames consist of structural steel beams joined to reinforced concrete columns. In the last decades, extensive research has been carried out for RCS structures because of the efficiency and economy in application for low to mid-rise structures in moderate to high seismic regions. This study aims to investigate the possibility of improvements or limitations of using RCS composite system for high rise RCS structures in regions of high seismicity. This paper presents the results of a parametric study using a finite element analysis. The study involves both linear elastic time history as well as design response spectrum analyses. The parametric study involves the effect of material (reinforced concrete and steel), plan aspect ratio, floor height and beam span.Â  The findings indicate that the use of RCS composite material not only provides a more economic solution, but also increases efficiency in terms of resilience towards dynamic loadings that the structure may be subjected to due to earthquake actions especially in high seismic regions.Â